Effects of dietary fibre and protein content on intestinal fibre degradation, short-chain fatty acid and microbiota composition in a high-fat fructose-rich diet induced obese Göttingen Minipig model. Issue 12 (24th November 2020) - Xu, Yetong; Curtasu, Mihai Victor; Bendiks, Zachary; Marco, Maria L.; P. Nørskov, Natalja; Knudsen, Knud Erik Bach; Hedemann, Mette Skou; Lærke, Helle Nygaard
Abstract : An AX-enriched high DF diet improved the intestinal environment and attenuated protein fermentation, while protein did not show prebiotic effects. Abstract : Obesity-related metabolic syndrome has been linked with gut microbiome dysbiosis while dietary fibre (DF) and protein can modify the gut microbial ecosystem and metabolism. After 20-weeks of high-fat fructose-rich diet feeding for the development of obesity, forty-three 30-week old Göttingen Minipigs (31 ± 4.0 kg body weight) were allocated to one of the four diets with low or high DF and protein contents in a two by two factorial design and digesta were collected from the intestinal segments of minipigs after 8 weeks at libitum feeding. High DF content increased ( P < 0.001) while high protein content decreased ( P = 0.004) the content of non-starch polysaccharides (NSP) in all intestinal segments. Arabinoxylan (AX) as proportion of NSP was higher with high DF ( P < 0.001) but decreased from the distal small intestine to the mid colon ( P < 0.001). High DF increased the relative abundance of Blautia, Faecalibacterium and Peptococcus in the caecum, the mid colon and faeces, reduced the intestinal concentrations of total short-chain fatty acids (SCFA) ( P = 0.020) and acetate ( P = 0.011) but slightly increased butyrate pools in the large intestine ( P ≤ 0.050) compared to low DF. High protein increased the SCFA ( P = 0.026) and propionate ( P = 0.044) concentrations in the gut. High DF induced a lower increase in the BCFA concentration and proportion throughout the colon ( P < 0.001). The butyrate concentrations in plasma from the jugular vein were increased with high DF diets ( P = 0.031), whereas the propionate concentrations were increased ( P < 0.001) and succinate were decreased ( P = 0.001) with high protein diets compared with low protein diets. In conclusion, AX in the high DF diets was continuously degraded up to the mid-colon, associated with enriched butyrate-producing bacteria and slightly improved butyrate production, while protein fermentation was attenuated by high DF and high protein did not show prebiotic effects in this obese minipig model.